The Influence of Human Resource Competence and Work Motivation on Traders’ Work Spirit in Tegal Gubug Traditional Market - Mega Safitri; Dharliana Hardjiwikarto; Juwita (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of human resource competence and work motivation on the work spirit of traders in the Tegal Gubug Traditional Market. The research employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to 96 trader respondents and analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that human resource competence and work motivation have a positive and significant effect on traders’ work spirit, both partially and simultaneously. Work motivation is identified as the most dominant factor in enhancing work spirit. This study is expected to serve as a reference for market management and local governments in designing trader development programs.